2011
DOI: 10.1186/1471-2458-11-490
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sexual partners and condom use among 10 - 19 year-olds in four districts in Tanzania: What do we learn?

Abstract: BackgroundAlthough some studies in Tanzania have addressed the question of sexuality and STIs among adolescents, mostly those aged 15 - 19 years, evidence on how multiple sexual partners influence condom use among 10 - 19 year-olds is limited. This study attempts to bridge this gap by testing a hypothesis that sexual relationships with multiple partners in the age group 10 - 19 years spurs condom use during sex in four districts in Tanzania.MethodsSecondary analysis was performed using data from the Adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
51
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 22 publications
9
51
4
Order By: Relevance
“…This observation is probably linked to the fact that male respondents are generally more mobile and have more access to information on condoms and the ability to buy condoms (Ochieng et al, 2011). However, our finding is in contrast with previous investigators in Tanzania, who found that condom use was higher among females than males (Exavery et al, 2011). The most important explanatory factor to this observation may be gender power differences in condom use among male and female participants (Prata, Vahidnia, & Fraser, 2005).…”
Section: Discussioncontrasting
confidence: 99%
“…This observation is probably linked to the fact that male respondents are generally more mobile and have more access to information on condoms and the ability to buy condoms (Ochieng et al, 2011). However, our finding is in contrast with previous investigators in Tanzania, who found that condom use was higher among females than males (Exavery et al, 2011). The most important explanatory factor to this observation may be gender power differences in condom use among male and female participants (Prata, Vahidnia, & Fraser, 2005).…”
Section: Discussioncontrasting
confidence: 99%
“…Engaging in sexual relationships with multiple partners is a risky behaviour [27] and emphasis has always been centering on condom use at each risky intercourse to ensure protection against STIs including HIV [27,50]. Therefore, it may be because of perceived risk of contracting STIs especially HIV that women with multiple sexual partners were more likely to use condoms.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of multiple sexual partners among Tanzanian college students was 42%; males were two times more likely to have multiple sexual partners compared to females [12].…”
Section: Introductionmentioning
confidence: 92%